The structure and texture genesis of apatite-type lanthanum silicates during their synthesis by co-precipitation. Issue 10 (December 2015) - Kharlamova, Tamara; Vodyankina, Olga; Matveev, Alexander; Stathopoulos, Vassilis; Ishchenko, Arcady; Khabibulin, Dzhalil; Sadykov, Vladislav
Abstract: Peculiarities of genesis of the structure and texture of apatite-type lanthanum silicates, both undoped and doped with aluminum, in the course of co-precipitation followed by sediment thermal treatment were elucidated by using a combination of methods including thermal analysis, XRD, IR spectroscopy, low-temperature adsorption of nitrogen, 27 Al and 29 Si MAS NMR spectroscopy and TEM with EDX analysis. An amorphous lanthanum silicate with the short-range ordering typical for ortho-diorthosilicate was shown to be formed in the course of precipitation, while its crystallization proceeds via rearrangement of the polymeric structure of primary particles during subsequent thermal treatment.